Mathematics Education Students' Perceptions of the Impact of Parental Involvement on Mental Health - Hidayat, Salma Nabilah; Umaami, Nayla Shofiyyatul; W, Wahyunengsih (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines mathematics education students' perceptions of the impact of parental involvement on their mental health. This study uses a quantitative approach through data collection by distributing an online questionnaire divided into three categories of questions, namely cognitive aspects, affective aspects, and psychomotor aspects, to 32 respondents. From the average obtained, the results stated agreement with the statements in the questionnaire, reaching 75% choosing Strongly Agree and Agree. Here, it shows that, in general, mathematics education students have a positive tendency in terms of responding to parental involvement. It is proven that many of them experience high academic pressure due to parental expectations. The form of impact that arises due to this pressure is anxiety, fear of failure, emotional stress, and open communication between parents and students to reduce academic stress and maintain mental well-being. This study shows a need for balanced parental involvement, which supports children without feeling burdened.